SUBSTANSI MANAJEMEN STRATEGIK LEMBAGA PENDIDIKAN - Syihabuddin, Muhammad Arif (Universitas Kiai Abdullah Faqih Gresik, 2023)
Abstrak: This study examines the substance of management strategy in educational institutions. Management is one of the main components in education system, this component has the function including “planning”, “organizing”, “implementing”, and “assessing” or “supervising” the education system. Strategic management is a systematic approach to management responsibility, conditioning the organization into a position that is sure to achieve its objectives in a way that ensures success, that is sustainable and makes the institution guarantee or secure a surprising format. There are four key attributes in strategic management, namely: 1) Directed directly at all goals and objectives of the organization; 2) Involve various stakeholders in decision making; 3) Be proportioned to short-term and long-term perspectives; 4) Determine the trade-off between efficiency and effectiveness. In strategic management there are stages that include strategic formulation, strategic implementation, and strategic evaluation. Kata kunci: Education Management, Strategic Management, Educational Institutions